(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the this paper we introduced a class of Multivalent functions with negative coefficients defined by Dziak-Srivastava operator and some application of Fractional Calculus , we obtain some theorems of this class. Mathematics subject classification:30C45.